A Matlab toolbox for Global Sensitivity Analysis. (August 2015) - Pianosi, Francesca; Sarrazin, Fanny; Wagener, Thorsten
Abstract: Global Sensitivity Analysis (GSA) is increasingly used in the development and assessment of environmental models. Here we present a Matlab/Octave toolbox for the application of GSA, called SAFE (Sensitivity Analysis For Everybody). It implements several established GSA methods and allows for easily integrating others. All methods implemented in SAFE support the assessment of the robustness and convergence of sensitivity indices. Furthermore, SAFE includes numerous visualisation tools for the effective investigation and communication of GSA results. The toolbox is designed to make GSA accessible to non-specialist users, and to provide a fully commented code for more experienced users to complement their own tools. The documentation includes a set of workflow scripts with practical guidelines on how to apply GSA and how to use the toolbox. SAFE is open source and freely available for academic and non-commercial purpose. Ultimately, SAFE aims at contributing towards improving the diffusion and quality of GSA practice in the environmental modelling community. Highlights: SAFE implements several GSA methods and can easily integrate new ones. SAFE facilitates assessment of robustness/convergence and effective visualization. SAFE embeds good practice guidelines through workflow scripts. SAFE is intended for both non-specialists users and SA developers.